Pengaruh Promosi Dan Brand Ambasador Terhadap Keputusan Pembelian Sepatu Pada PT. Sepatu Bata Tbk. Cabang Karawang - Florentina Stefhani Nainggolan; Asep Maulana Novianto (UNHI Press, 2022)
In the current era and the increasing market demand in the fashion industry, the world is currently increasingly aggressively developing clothing models that are in line with current developments. The purpose of this study was to determine the effect of promotion and brand ambassadors on purchasing decisions at PT. Shoes Bata Tbk. Karawang Branch. The sample in this study is as many as 100 respondents from customers Shoes Bata Karawang Branch. This research uses the descriptive verification method. The sampling technique used in this study was disproportionate stratified random in determining the number of samples using the Slovin formula with an error rate of 10%. The type of data used in this study is to use secondary and primary data. The data analysis technique used is simple linear regression. The results of this study indicate that promotions and brand ambassadors influence purchasing decisions.